Sustainable Construction Integration Theory (SCIT): A triple-layer approach an empirical study of technical, operational, and organizational integration - Joni Kutu' Kampilong; Anneke Elisabeth Rattu; Nicolas Willem James Mandagi (World Development Sustainability)
Environmental concern and the stringent regulations of the construction sector are leading to increasing pressure for the adoption of sustainable practices; however, this is accompanied by technical, operational, and organizational challenges. Little is known about how these factors, taken together, affect implementation effectiveness. Through the first empirical validation of Sustainable Construction Integration Theory (SCIT), this study examines the complex dynamics between the technical, operational, and organizational layers of sustainable construction. Through structural equation modeling with thematic analysis of 429 building projects, this research demonstrates HRC and Performance (β = 0.38, p < 0.001) interactions, as well as the critical moderating role of organizational commitment and support (OCS). The second finding indicates that HRC acts as a mediator between technical and operational characteristics and the outcomes of implementation (Q2 = 0.695). The results also show that energy efficiency has a big effect on how sustainable a project is (β = 0.42, p < 0.001), and that capacity and organizational barriers are very important things to think about when putting the plan into action, as they cause 16 % of implementation problems. This study leverages institutional theory and the dynamic capacity framework to demonstrate that SCIT enhances the implementation success rate by 38 percent. These insights contribute to practical guidelines for sustainable construction organizations that emphasize combined human resource development and robust organizational support for sustainable outcomes.